PERSINGGUNGAN KONSTITUSI, IDEOLOGI DAN AGAMA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA DI INSONESIA PADA ERA REFORMASI - Sukirno (Universitas Islam Indonesia, 2022)
The 1945 Constitution of the Republic of Indonesia (UUD 1945), the ideology of Pancasila and Religion are the three main foundations of the life of the nation in Indonesia, each has a wedge that must be implemented synergistically and harmoniously. Historical facts prove that the intersection of the 1945 Constitution, Pancasila and Religion has always been a dialectic, even though the academic debate is considered finished and final. In the reform era, the clash of the 1945 Constitution, Pancasila and Religion resurfaced through the thoughts and real actions of community organizations and community groups, thus endangering the integrity of Republic of Indonesia. This paper is a normative juridical study with qualitative analysis to answer why in the reform era the intersection of the 1945 Constitution, Pancasila, and Religion (especially Islam) was still debated. This paper is a normative juridical study with qualitative analysis to answer why in the reform era the intersection of the 1945 Constitution, Pancasila, and Religion (especially Islam) was still debated. The results of this study prove that because it is an expression of the freedom of human rights and democratization guaranteed by the 1945 Constitution of the Republic of Indonesia. In addition, there are still radical and intolerant groups that consider Pancasila and the 1945 Constitution of the Republic of Indonesia to be contrary to religious teachings. Persinggungan konstitusi, ideologi dan agama seringkali diperdebatkan dan dibenturkan. Ketiganya merupakan landasan berbangsa dan bernegara, namun ideologi dan agama acapkali dianggap sebagai dua kutub yang saling bertentangan. Tulisan ini merupakan kajian yuridis normatif dengan analisis kualitatif berdasarkan pendekatan historis-sosiologis terhadap masalah posisi UUD 1945,Pancasila, dan Agama (Islam), serta pola persinggungan ketiganya dalam kehidupan berbangsa dan bernegara di Indonesia pada Era Reformasi. Fakta historis membuktikan, persinggungan UUD 1945, Pancasila dan Agama selalu menjadi sebuah dialektika, meskipun perdebatan akademis sudah dianggap selesai dan final. Pada era reformasi, pembenturan UUD 1945, Pancasila dan agama mencuat kembali yang oleh Pemerintah kemudian ditindak tegas dengan alasan penegakan UUD 1945 dan Pancasila, serta menjaga keutuhan NKRI.